Examination of foreign language classroom anxiety and achievement in foreign language in Turkish University students in terms of various variables - Doğan, Yunus; Tuncer, Murat (My University, 2016)
This correlational survey study aimed to investigate whether the Turkish prep-class students’ foreign language classroom anxiety levels and foreign language achievement significantly differ in terms of such variables as their gender, their experience abroad, perceived level of income and any third language (other than Turkish and English) they knew. Moreover, the study also tried to identify whether the sub-dimensions of the foreign language classroom anxiety scalespeaking anxiety in language class, interest towards language class and anxiety of talking with native speakersignificantly differ in terms of the independent variables afore-mentioned. And the last aim of the study was to understand whether there is any significant correlation between the foreign language classroom anxiety and foreign language achievement. The participants of the study was consisted of 683 students who, having been registered to study at various engineering departments of Fırat University, were receiving compulsory English preparatory education at the School of Foreign Languages during the academic year of 2013-2014. In order to measure the students’ foreign language classroom anxiety, the scale developed by Horwitz, Horwitz& Cope (1986) and adapted into Turkish by Gürsu (2011) was used. The grades of the students were taken from the School of Foreign Languages. For data analysis, such statistical tests as percentage, frequency, t-test, ANOVA, eta-squared and Pearson’s Correlation were employed. As a result, it was understood that there is a negative correlation between foreign language classroom anxiety and foreign language achievement.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Language anxiety; Language achievement; Gender; Economic status; Experience abroad